Development of a community-informed communication toolkit to prevent spread of viral illness in schools, including SARS-COV-2 - Summers, August; Calderon, Gabriela V.; Klein, Lauren M.; Wang, June; Dinh, Janny; Suliman, Tina; Hager, Erin R.; Edwards, Lorece; Collins, Megan E.; Johnson, Sara B. (Frontiers in Public Health, 2023)
Introduction Schools were uniquely impacted during the COVID-19 (SARS-COV-2) pandemic. We sought to elucidate how parents/guardians of elementary and middle school students in Maryland navigated the return to in-person school following remote instruction. We also sought to understand how they perceived communication about school-based COVID-19 mitigation strategies and their preferences for the content and format of public health communication about COVID-19 mitigation in schools. Methods We engaged a community advisory board comprised of key partners and implemented a survey and focus groups. Results Results indicated that parents/guardians wanted clearer communication about COVID-19 mitigation policies in schools and were experiencing fatigue and confusion. These insights informed the development of a tailorable communication toolkit. The toolkit was designed to (1) inform parents/guardians about the importance and effectiveness of mitigation strategies for preventing viral spread to keep children in school, (2) promote a sense of community and support, and (3) help school communication teams effectively communicate information about mitigation strategies being implemented. Discussion We describe a process for leveraging schools as a trusted messenger, engaging school communities in the development of communication messages, and utilizing a tailorable communication toolkit in the context of shifting public health guidance and local needs. The toolkit development and dissemination process offers a model for targeting public health messaging to parents/guardians in school settings.